Reclaim your relationship : - Potter-Efron, Ronald T. (Wiley, 2006)
The simple phrase "I love you" is terribly important to people–so what keeps so many of us from saying it? In Reclaim Your Relationship, Ron and Pat Potter-Efron, marriage therapists who have been married for 37 years, combine their real-life and clinical experience in this practical and accessible workbook designed to help individuals improve connections in their relationships with those they love. Presenting engaging, hands-on exercises, the authors help readers learn to say "I love you" to their partners with ease and genuine meaning, show their partner love through consistent acts of caring, and take in their partner’s loving words and deeds without always demanding more.